Performance and grazing strategy of pelibuey sheep fed with different levels of protein: Estrategia de pastoreo de ovinos pelibuey - Cruz-Hernández, Aldenamar; Cámara-Acosta, Jesús; Chay-Canúl, Alfonso Juventino; Rojas-García, Adelaido Rafael; Ventura-Rios, Joel; Ramírez-Vera, Santiago (Ecosistemas y Recursos Agropecuarios, 2021)
With the objective of evaluating the performance of Pelibuey lambs fed with different levels of protein and Tanzania grass at two rotational grazing regimes. It was used completely random design. Were used 30 ewes of the Pelibuey breed with an initial live weight of 20.33 ± 1.56 kg, which were distributed in 30 pens of 2.5 m long x .80 m wide and in a 1.5 ha pasture divided into 0.25 ha. The animals were fed at 07:00 am and at 16:00 pm. With diets containing 10, 12, 14, 16% CP and a control feed, the lambs were grouped and grazed in pastures at two intensities of 9-11 cm and 13-15 cm of residual height. Were evaluated dry matter (DM), growth rate (TC), bromatological analysis of the pasture and weight gain. The highest accumulation of MS and TC were obtained in the months of June and July. The residual height of 9-11 cm presented the highest content of crude protein (CP) and neutral detergent fiber (NDF). The highest values ​​in weight gain were obtained in lambs that grazed in pastures at a residual height of 9-13 cm and that were supplemented with food with 14 and 16% CP. The Tanzania grass presented good DM production and morphological components at an intensity of 13-15 cm. While the lambs that were fed 16% CP in the ration presented the highest daily weight gains.